An Improbable Amino‐Functionalized Fullerene Spacer Enables 2D/3D Hybrid Perovskite with Enhanced Electron Transport in Solar Cells. (11th June 2022) - Zhou, Weiran; Jia, Lingbo; Chen, Muqing; Li, Xingcheng; Su, Zhenhuang; Shang, Yanbo; Jiang, Xiaofen; Gao, Xingyu; Chen, Tao; Wang, Mingtai; Zhu, Zonglong; Lu, Yalin; et al.
Abstract: 2D perovskites possess superior humidity stability but inferior power conversion efficiency (PCE) compared with 3D perovskites due to their typically insulating spacers. Size of the spacer cation is determinative for the formation of 2D perovskite, and fullerene is believed not to be capable of templating 2D perovskite structure because of its larger size than the width of the lead‐halide octahedron despite its well‐known strong electron‐accepting ability. Herein, a novel amino‐functionalized fullerene derivative (abbreviated as C60 ‐BPAM) is developed and an 'improbable' spacer for 2D/3D hybrid perovskite solar cells (PSCs), achieving enhanced electron transport is applied. Unlike most of the reported alkylammonium spacers that are based on insulating organic tails, the incorporation of a highly conductive fullerene tail within C60 ‐BPAM 2+ leads to increased electron density in 2D/3D perovskite and induces an additional built‐in electric field, facilitating electron transport in PSCs. Besides, the 2D/3D hybrid structure helps to passivate both of the shallow‐ and deep‐level defects within perovskite. As a result, the PCE of 2D/3D PSCs improves from 19.36% (3D MAPbI3 PSCs) to 20.21%. Moreover, the 2D/3D PSCs show significant improvement in the humidity stability compared to the 3D counterparts. Abstract : A novel amino‐functionalized fullerene derivative ( C 60 ‐BPAM) is synthesized and applied as an 'improbable' spacer cation for 2D/3D hybrid perovskite affording enhanced electron transport, which represents the first fullerene spacer and the largest aromatic spacer applicable in 2D/3D perovskite solar cells (PSCs). Incorporation of C 60 ‐BPAM 2+ spacer bearing highly conductive fullerene tail leads to increased PCE of 2D/3D PSCs from 19.36% to 20.21% along with significantly improved humidity stability.